A frame-shift deletion in the PURA gene associates with a new clinical finding: Hypoglycorrhachia. Is GLUT1 a new PURA target? - Mayorga, Lía (2018)
PURA is a DNA/RNA-binding protein known to have an important role as a transcriptional and translational regulator. Mutations in the PURA gene have been documented to cause mainly a neurologic phenotype including hypotonia, epilepsy, development delay and respiratory alterations. We report here a patient with a frame-shift deletion in the PURA gene that apart from the classical PURA deficiency phenotype had marked hypoglycorrhachia, overlapping the clinical findings with a GLUT1 deficiency syndrome. SLC2A1 (GLUT1) mutations were discarded, so we hypothesized that GLUT1 could be downregulated in this PURA deficient scenario. We confirmed reduced GLUT1 expression in the patient's peripheral blood cells compared to controls predicting that this could also be happening in the blood-brain barrier and in this way explain the hypoglycorrhachia. Based on PURA's known functions as a transcriptional and translational regulator, we propose GLUT1 as a new PURA target. Further in vitro and in vivo studies are needed to confirm this and to uncover the underlying molecular mechanisms.